The relationship between selected organizational culture and employees' turnover intentions - Ng, Kee Kee. (Universiti Malaysia Sarawak, UNIMAS, 2010)
E mployees tend to demonstrate turnover intentions when organization c ulture was not match with their expectation . The main objective of this study is to determine the relationship between organization culture and employees’ turnover intention in an organization. Four organization culture were selected namely job challenge, teamwork, innovation and fairness. Sixty re spondents from a selected construction organization were participated in this study and the data was analyzed by using Statistical Packages for the Social Sciences (SPSS) Version 17. T - Test, ANOVA, Pearson Coefficient Correlation and Simple Linear Regressi on were used to test the research hypotheses. Findings of this study showed that all four selected organization culture have a significant and weak negative relationship with employees’ turnover intention in that particular organization . Results also showe d there is no difference between selected respondents from difference demographic characteristics (gender, age and education) level in term of their turnover intention. I nnovation was the dominant factor among all independent variables that influencing emp loyee’s turnover intention in an organization. Therefore, this study provides a perspective on link between organization culture and turnover intention among their employees. It is suggested to the management can effectively manage employees’ turnover inte ntions by emphasis on the norms of organization cultures.